Enhanced mechanical properties and consolidation of the ultra-fine WC–Al2O3 composites using pulsed current activated heating. Issue 7 (15th May 2016) - Oh, Seung-Jin; Kim, Byung-Su; Yoon, Jin-Kook; Hong, Kyung-Tae; Shon, In-Jin
Abstract: The rapid sintering of ultra-fine WC–Al2 O3 composites in a short time was investigated with a focus on the mechanical properties and consolidation using pulsed current activated sintering. The advantage of this process is that it allows very quick densification to near theoretical density and prohibition of grain growth in nanomaterials. The addition of Al2 O3 to WC can facilitate consolidation and improve mechanical properties. The hardness and fracture toughness of WC–Al2 O3 composites outperform those of monolithic Al2 O3 .